On optimal fast solutions to the problem of gossiping by letters - Salerni, Giulio (Utilitas Mathematica, 2004)
We determine a fast solution to the problem of gossiping by letters, for a number n of persons, 2s < n ≤ 3·2s-1 (s positive integer), which requires only 3n - 4 letters, instead of n[log 2 n] as in the classical solution by Entringer and Slater [1]. We conjecture that our solution is optimal.